Economic Survey of Latin America and the Caribbean 2004-2005 - Commission économique pour l'Amérique latine et les Caraibes (United Nations, 2005)
This year's edition of the Economic survey of Latin America and the Caribbean,the fifty-seventh in this series, is divided into two parts. The first analyses the main features of the regional economy, while the second examines the situation in the individual countries of Latin America and the Caribbean. The full statistical appendix is published in electronic format for ease of data processing.